Beeldenpark Drechtoevers 1996. - Arend, Lucien den; Augustijn, Piet; Blaak, John; Corporaal, Dirk; Meeuwis, Meeno; Popijus, Kees; Nederlandse Kring van Beeldhouwers (Zwijndrecht : Stichting Vriendenkring Beeldenpark Drechtoevers, 1996)
Arend, Lucien den ; Arons, Lukas ; van Bennekum, Henk ; Blaauw, Gjalt ; Buckens, Kees ; Goerres, Nina ; van Gulik, Cor ; Hettema, Renze ; d'Hont, Pieter ; Kalle, Ton ; Knops, Egidius ; Lamberts, Aart ; Lixenberg, Cyril ; Lous, Niels ; Pieters, Godfried ; Shields, Mari ; Spronken, Arthur ; van Spronsen, Erik ; Teeuwen, Marry ; Teeuwen, Roel ; Timmer, Jan ; Vanèn, Frits ; Verhoeven, Adri ; de Wit, Niko ; Zanstra, Margot
Nederlands
boek